THE IMPACT OF DIGITAL LEARNING PLATFORM ON ADOLESCENTS’ SPEAKING ABILITY - Zai, Oktario Kurniawan; Tarigan, Fatin Nadifa; Gulo, Hariani (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2024)
The majority of Indonesian adolescent are familiar with digital platform either in academic setting or in social context. This research aims to describe the effect of digital learning platform on adolescents’ speaking ability. The research method used was quasi experimental design with data collection techniques using observation and tests. The population was the teenagers consists of 50 people in English Student Association Club and was taken by using purposive sampling techniques. Data collection was carried out through pre-test and post-test. Calculating the data using the t test concluded that Ha was accepted or approved and Ho was rejected. The results of data processing show that the highest frequency of participants in both the experimental and control groups was observed in the 55-64 interval while the experimental group exhibited a higher concentration of participants with scores in the upper-mid range (85-94 interval). In contrast, the control group showed a more even distribution across the intervals, with fewer participants scoring in the highest range (95-100 interval). This result indicates digital learning platform has a potential positive effect on adolescents’ speaking ability.